Antidiabetic and antihyperlipidemic activities of a novel polyherbal formulation in streptozotocin - nicotinamide induced diabetic wistar rats - KISHOR KUMAR V; LALITHA K G (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: To investigate the antidiabetic and antihyperlipidemic activities of polyherbal formulation (PHF) containing seven plants namely Cassia auriculata, Cassia fistula, Syzygium cumini, Cyperus rotundus, Saussurea lappa, Terminalia arjuna and Salacia reticulate in streptozotocin (STZ) - nicotinamide (NC) induced diabetic rats by administering oral doses (200 and 400 mg/kg body weight). Materials and Methods: Animals were divided into diabetic and nondiabetic groups. Rats were fed with normal laboratory diet and induced with a single intraperitoneal injection of 60mg/kg of STZ, and thereafter 120 mg/kg NC was injected after 15min. Diabetic rats were treated with formulation (200 and 400 mg/kg) and glibenclamide 5 mg/kg. Blood glucose levels were measured using blood glucose test strips with ACCU CHEK glucometer. Glycosylated haemoglobin, total haemoglobin, lipid profiles, lipoproteins, hepatic marker enzymes activity were determined in normal and STZ- NC induced diabetic rats after oral administration of the PHF for 28 days. Histopathological changes in normal and diabetic rat pancreas organs were also observed after PHF treatment.The statistical analysis of results was carried out using one-way analysis (ANOVA) followed by post hoc multiple comparison tests. Results: Treatment of diabetic rats with PHF (200 and 400 mg/kg) and glibenclamide (5 mg/kg) indicate significant decreased blood glucose level and significant improvement in body weight. PHF treated rats showed significant (P < 0.01) decrease in the level of HbA1C, TC, TG, LDL, VLDL, AST, ALT and ALP while a significant increment in the level of Hb, HDL cholesterol was observed. Furthermore, the PHF treated rats has a favourable effect on the histopathological changes of the pancreas in STZ-NC induced diabetes. Conclusion: These findings suggested the antihyperglycemic and antihyperlipidemic properties of the PHF and thus help in preventing future complications of diabetes.